De la ontología somática a la pedagogía corporal - Quintas Hijós, Alejandro (Studi sulla Formazione/Open Journal of Education, 2024)
This study develops a new ontology of the body, beginning by examining Western idealism and dualism, to propose somatic visions more aligned with monism, materialism, and pragmatism. Subsequently, it is complemented by an analysis of the body as a traditional object of pedagogical power and its political, social, and educational implications. Finally, it establishes a pedagogy that begins with, is based on, and returns to the body as nature.